2014
DOI: 10.1038/eye.2014.126
|View full text |Cite
|
Sign up to set email alerts
|

Medical therapy for uveal effusion syndrome

Abstract: Purpose To report a case series of three patients with bilateral uveal effusion syndrome (UES), treated conservatively with oral carbonic anhydrase inhibitors and topical prostaglandin analogues (PAs). Methods Three patients with bilateral UES were treated with the same initial therapy. Topical PA latanoprost 0.005% and acetazolamide 250 mg were administered in order to reduce intraocular pressure, improve uveoscleral outflow, and facilitate resolution of uveal effusion. Results The chorioretinal detachment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…11 Furthermore, prostaglandin administration could reduce scleral collagen levels by increasing scleral metalloproteinase levels, thus stimulating the pump mechanism of the retinal pigment epithelium and facilitating reabsorption of the fluid. 11 , 14 Psychological factors might also have contributed to recovery because, during treatment for the second instance of ERD, the patient was calmer and more relaxed than during treatment for the first instance of ERD. It has been shown that long-term anxiety can cause imbalances in certain chemicals, such as 5-hydroxytryptamine, norepinephrine, and dopamine, leading to disturbances in body functions, such as local edema and stress-induced inflammatory exudation.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, prostaglandin administration could reduce scleral collagen levels by increasing scleral metalloproteinase levels, thus stimulating the pump mechanism of the retinal pigment epithelium and facilitating reabsorption of the fluid. 11 , 14 Psychological factors might also have contributed to recovery because, during treatment for the second instance of ERD, the patient was calmer and more relaxed than during treatment for the first instance of ERD. It has been shown that long-term anxiety can cause imbalances in certain chemicals, such as 5-hydroxytryptamine, norepinephrine, and dopamine, leading to disturbances in body functions, such as local edema and stress-induced inflammatory exudation.…”
Section: Discussionmentioning
confidence: 99%
“…Table 6 presents outcomes of various medical therapies to treat UES in recent reports. This includes steroids, topical NSAIDs, prostaglandin analogues, carbonic anhydrase inhibitors, anti-VEGF, or a combination of medical therapies [55][56][57][58].…”
Section: Emerging Medical Therapiesmentioning
confidence: 99%
“…This includes steroids, topical NSAIDs, prostaglandin analogues, carbonic anhydrase inhibitors, anti-VEGF, or a combination of medical therapies [ 55 58 ].…”
Section: Emerging Medical Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism behind this may be that VEGF can reduce the activation of macrophages and further regulate the expression of IL-6 and IL-8 [ 71 , 72 ]. The reports of Park and Andrijevic Dert et al [ 73 , 74 ] show that oral carbonic anhydrase inhibitors and local prostaglandin analogues can help the absorption of subretinal fluid and improve the detached choroid and retina in nanophthalmic eyes with UES. There may be two possible mechanisms for this: on one hand, the prostaglandin analogues decrease the level of scleral collagens by increasing the level of scleral metalloproteinase, thus regulating the flow of fluids through the sclera and increasing the permeability of scleral macromolecules [ 75 ].…”
Section: Treatments For Uveal Effusion Syndrome In Nanophthalmic Ementioning
confidence: 99%